Pilot Study of Trace Elements in the Infusion of Medicinal Plants Used for Diabetes Treatment. (18th April 2022) - Brima, Eid I.; Siddeeg, Saifeldin M.
Abstract : The purpose of this study was to evaluate trace element contents in different medicinal plants used for diabetes treatments by residents in Asir region. Five medicinal plants—Tut leaves ( Mulberry ), olive leaves ( Olea europaea ), clove ( Syzygium aromaticum ), Luban Dhakar ( Boswellia carterii ), and Karela or bitter melon ( Momordica charantia )—were collected from two cities, Khamis Mushait and Abha, in the Asir region, Saudi Arabia. Infusions (hot water extracts) were obtained from each plant, and elemental analysis was conducted using inductively coupled plasma mass spectrometry (ICP-MS). Fourteen elements (Al, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Sr, Cd, Ba, and Pb) were measured in all plants. The results revealed that the fourteen elements were present at different levels (µg/g) in all plants. Momordica charantia exhibited high levels of essential (Mn (251.4), Co (1.18), Cu (54.64), and Se (2.18)) and toxic elements (Al (39.20), As (0.57), Cd (0.33), and Pb (4.48)), followed by Syzygium aromaticum (Mn (736.36)) and Boswellia carterii (Pb (0.93)), which exceeded the PMTDI in traditional doses used for diabetes treatments. However, Mulberry and Olea europaea did not exceed the daily guideline values for all elements. Based on our findings, we cautiously recommend the latter two plants for the traditional treatment of diabetes, because they are not considered as source of harm based on their levels of elements. Their use should be restricted by comprehensive compound analysis to guarantee their safe use.